The effect of tennis batting sound on anxiety: a randomized controlled trial and basic acoustic analysis - Wang, H.; Zhang, G.; Li, X.; Pu, S. (Frontiers in Psychology, 2023)
Purpose To investigate the potential role of the unique sound of tennis in alleviating anxiety. Previous research has consistently shown that exercise can mitigate anxiety, primarily attributed to the impact of increased physical activity on hormonal and neurostructural changes. However, in daily life we find that one of the reasons people are drawn to tennis is its distinctive sound. In this study, we specifically examined the influence of this sound on anxiety.